Empowering E-Learning as An Interactive Teaching For Arabic Learners - Nuril Mufidah; Saidna Zulfiqar Bin Tahir (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2018)
AbstractThis research attempts to explore the implementation of blended learning in teaching the course of ‘Qawaid al-Imla 1’ and the perceptions of teachers and students towards the blended learning application at UIN Maulana Malik Ibrahim Malang. It applied a grounded theory design using the observation and interview to collect the data. The data gained were analyzed using Strauss & Corbin model, they are, open coding, axial coding, and selective coding. The results found that application of blended learning helped the lecturers in planning and presenting the material as well as the evaluating the students’ learning progress. The students perceive good in the implementation of blended learning provided by the university.Keywords: blended learning, hybrid learning, Arabic, qawaid imla’ تمكين التعليم الإلكتروني كالدراسة التفاعلية للمتعليمن العربيةنورل مريدة، سعدنا زلفقار بن تاهيرالجامعة الإسلامية الحكومية مولانا مالك ابراهيم مالانج، جامعة إقراء بورو، مالوكوnurilmuridah86@uin-malang.ac.id, saidnazulfiqar@gmail.com يحاول هذا البحث استكشاف عن تطبيق التعلم المختلط فى تدريس المادة "قواعد الإملاء 1" و تصورات المعلمين والطلبة نحو هذا تطبيق التعلم المدمج فى الجامعة الإسلامية الحكومية مولانا مالك إبراهيم مالنج. استخدمت الباحثة نظرية التصميم التطبيقي لهذا البحث التى تحتوي على الملاحظة والمقابلة لجمع البيانات. وتم تحليل البيانات المكتسبية باستخدام نموذج ستراوس و كوربين (Strauss & Corbin)، وهي التشفير المفتوحى، التشفير المحوري و التشفير الانتقائي. والنتيجة هي بأن تطبيق التعلم المختلط يساعد كثيرا المحاضرين والمدرسين فى التخطيط وتقديم المواد المدروس كما هو فى تقيــيم عن تطوّر التعلم لدي الطلاب. وكان الطلاب يقدرون على التنفيذ جيدا لهذا برنامج التعلم المختلط الذي تقدمه الجامعة.الكلمة الرئيسية: التعلم المختلط، تنفيذ طريقة التعليم، اللغة العربية، الطلبة، قواعد الإملاء.